Implementation of the Merdeka Curriculum in the Teaching of the Qur’an and Hadith - Aisyah Zahratunnisa; A. Markama; Andi Anirah; Putri Salsabila; Melviana Melviana (Faculty of Education and Teacher Training of UINSI Samarinda, 2026)
This study examines the implementation of the Merdeka Curriculum in Al-Qur’an Hadith instruction at MTsN 1 Palu City. Employing a qualitative descriptive approach, data were collected through classroom observations, semi-structured interviews with one Al-Qur'an Hadith teacher and three Grade VII students, and documentation review. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. Findings reveal that while teachers have adopted the required instructional frameworks, the practical application of differentiated instruction is significantly hindered by large class sizes (40 students per class) and disparities in students' Qur'anic literacy. Teachers address these challenges by conducting remedial sessions outside of school hours, maintaining strict instructional control over digital devices, and fostering mentor-like personal relationships with students. The study concludes that the effectiveness of the Merdeka Curriculum in a madrasa setting depends not only on administrative adherence but also on the teacher’s ability to balance firm classroom management with a humanistic, responsive approach to student needs. These findings offer practical implications for teacher professional development in managing diverse classroom environments.